2000
DOI: 10.1515/hf.2000.105
|View full text |Cite
|
Sign up to set email alerts
|

Pulping of Whole Jute Plant (Corchorus capsularies) by Soda-Amine Liquor

Abstract: Pulping of whole jute plant is done by sodium hydroxide and ethylenediamine (EDA) or monoethanolamine (MEA) within 1 hour of cooking. The pulp yield is considerably higher than for the control soda and kraft pulps. Pulps obtained are better in physical properties as compared to kraft and soda pulps. The apparent density of soda-EDA pulps decreases with the increase of EDA in the soda liquor whereas the apparent density of soda-MEA pulps increases with the increase of MEA in soda liquor. Keywords Delignificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Ammonia treatments have been used to improve the strength and shrink resistance of cotton and regenerated fabrics (Yanai and Shimizu 2006;Pandey and Nair 1975;Lewin et al 1974) and are being explored as pretreatments for biomass to improve its conversion to glucose and biofuels (Teymouri et al 2005). Ethylenediamine (EDA) has also been investigated for its use in biomass pulping and pretreatment (Jahan and Farouqui 2000;Zargarian et al 1988) and as a component of cellulose solvents (Xiao and Frey 2007). In order to understand the detailed interaction of amines with cellulose and cellulosic biomass fibers we have been studying these interactions using a variety of crystallographic and spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia treatments have been used to improve the strength and shrink resistance of cotton and regenerated fabrics (Yanai and Shimizu 2006;Pandey and Nair 1975;Lewin et al 1974) and are being explored as pretreatments for biomass to improve its conversion to glucose and biofuels (Teymouri et al 2005). Ethylenediamine (EDA) has also been investigated for its use in biomass pulping and pretreatment (Jahan and Farouqui 2000;Zargarian et al 1988) and as a component of cellulose solvents (Xiao and Frey 2007). In order to understand the detailed interaction of amines with cellulose and cellulosic biomass fibers we have been studying these interactions using a variety of crystallographic and spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of 10% EDA charge in kraft process, kappa number reached to 23.6. The slightly decreasing trend in pulp yield with increasing EDA addition may be explained by dissolution of hemicelluloses and lignin (Jahan and Farouqui 2000). This result indicated that substantial increase in alpha-cellulose in pulp, which could be attributed to the selective removal of hemicelluloses and stabilization of alpha-cellulose as indicated by .…”
Section: Effect Of Eda On Delignification and Pentosan Dissolution Frmentioning
confidence: 81%
“…Julien and Sun (1979) also observed better delignification when EDA was added in soda liquor. Jahan and Farouqui (2000) also showed improved delignification and higher pentosan dissolution in presence EDA in soda liquor. Presence of amine in soda liquor altered the molecular weights of the dissolved lignin fraction and delignification is also associated with negative reduction potential of pulping additive .…”
Section: Effect Of Eda On Delignification and Pentosan Dissolution Frmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, some authors have also used amines to pulp various raw materials such as beech, spruce, olive tree prunings, jute and cotton [172][173][174][175][176][177][178][179].…”
Section: Ammonia and Aminesmentioning
confidence: 99%